A Brief Note of Lato (Caulerpa racemosa) Harvest at Solong-on, Siquijor, Philippines - Wagey, Billy T; Bucol, Abner A (e-Journal BUDIDAYA PERAIRAN, 2014)
Abstract Nearly 30 years since an assessment on the local harvest of Caulerpa racemosa at Solong-on, Siquijor, we conducted a similar study in November 2013. Present CPUE of Caulerpa is significantly lower than it was in the 1980s. Probable factors attributing to this decline are briefly enumerated and discussed. Keywords: seaweed, lato, harvest, Siquijor, Philippines